What Do Learning Scientists Do? A Survey of the ISLS Membership. Issue 2 (3rd April 2017) - Yoon, Susan A.; Hmelo-Silver, Cindy E.
Abstract : This study responds to a question that people working in the field of learning sciences get asked regularly: What do learning scientists do? Earlier attempts to answer this question came from a need to define a new field of educational research. Now that the International Society of the Learning Sciences (ISLS) has grown into a robust and productive society, it is time to gain a more nuanced understanding of learning sciences research and practices—including where it takes place, for whom, and in what form—as defined by members of the learning sciences community. Here we report on the responses of 253 ISLS members to a survey conducted in 2014. We discuss implications of the findings in terms of the type of impact learning scientists have. We also discuss how these results might be used to advise prospective students and to create a vision for our future.